2014
DOI: 10.1002/jaba.167
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of methods for teaching receptive language to toddlers with autism

Abstract: The use of a simple-conditional discrimination training procedure, in which stimuli are initially taught in isolation with no other comparison stimuli, is common in early intensive behavioral intervention programs. Researchers have suggested that this procedure may encourage the development of faulty stimulus control during training. The current study replicated previous work that compared the simple-conditional and the conditional-only methods to teach receptive labeling of pictures to young children with aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
16
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 7 publications
5
16
1
3
Order By: Relevance
“…Collectively, these results suggest that establishing simple discriminations may not be a prerequisite for teaching conditional discriminations to some learners with autism, or that conditional discrimination preparations can efficiently teach this simple discrimination in the context of teaching more complex conditional discriminations, relative to teaching each skill in isolation. However, these findings have been reported with a relatively small (N = 8 participants across Grow et al, ; Grow et al, ; Gutierrez et al, ; Leaf et al, ; Vedora & Grandelski, ) and homogenous participant population (all studies were based in the United States with conditional sample stimuli presented in English). The purpose of the current study was to replicate and extend the research comparing simple‐to‐conditional relative to conditional‐only training methods.…”
mentioning
confidence: 90%
“…Collectively, these results suggest that establishing simple discriminations may not be a prerequisite for teaching conditional discriminations to some learners with autism, or that conditional discrimination preparations can efficiently teach this simple discrimination in the context of teaching more complex conditional discriminations, relative to teaching each skill in isolation. However, these findings have been reported with a relatively small (N = 8 participants across Grow et al, ; Grow et al, ; Gutierrez et al, ; Leaf et al, ; Vedora & Grandelski, ) and homogenous participant population (all studies were based in the United States with conditional sample stimuli presented in English). The purpose of the current study was to replicate and extend the research comparing simple‐to‐conditional relative to conditional‐only training methods.…”
mentioning
confidence: 90%
“…Os resultados do presente estudo se somam aos achados recentes (Grow et al, 2011;Grow et al, 2014;Gutierrez et al, 2009;Vedora & Grandelski, 2015) que indicam 1) que os procedimento de treino DSC e DC são eficazes para ensinar linguagem receptiva para crianças com autismo (ou seja, ambos os procedimentos levam à aquisição do repertório); mas 2) que um treino DC pode ser mais eficiente que um treino DSC no estabelecimento de linguagem receptiva em crianças com autismo (ou seja, o treino DC produz a aquisição do repertório em menos sessões e com menos exposição ao erro).…”
Section: Discussionunclassified
“…Tomados conjuntamente, os resultados dos treinos e dos pós-treinos apontam que no ensino de linguagem receptiva para crianças com autismo o treino de discriminações simples não é um requisito necessário (ver também Grow et al, 2011;Grow et al, 2014;Gutierrez et al, 2009;Vedora & Grandelski, 2015), mas que um treino DSC baseado no formato com uso de blocos de tentativas e mais de dois estímulos discriminativos desde o início do treino (e.g. Saunders & Spradlin, 1990) pode favorecer a manutenção do repertório aprendido.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Participants in the Grow et al () study were three children with ASD, and results showed that the RR procedure was more effective for seven of the eight training sets, across participants. These findings were later replicated, and although both procedures were effective in the establishment of receptive labels, the RR required fewer trials to mastery (Grow, Kodak, & Carr, ; Vedora & Grandelski, ).…”
Section: Introductionmentioning
confidence: 88%